Impact of Potentially Antioxidant Probiotic Strains on Fermentation Quality and Antioxidant Status in Alfalfa Silage - Bokang Qi; Xinyu Cai; Wenkang Wang; Pengfei Ma; Xianjun Yuan; Xiang Tan (Antioxidants)
The study aimed to characterize the antioxidant properties of isolated lactic acid bacteria (LAB) and assess their impacts on fermentation quality and antioxidant status in alfalfa silage. Two LAB strains of Lactiplantibacillus plantarum XY15 and Lactiplantibacillus plantarum XY20 and a reference strain of Pediococcus acidilactici J17 were subjected to antioxidant property evaluation. This was followed by inoculation into alfalfa silage. The DPPH (2,2-diphenyl-1-picrylhydrazyl) and hydroxyl (OH) radical scavenging activities and the glutathione peroxidase (GSH-Px) activity of the cell-free supernatants of L. plantarum YX15 and L. plantarum YX20 were significantly (p < 0.05) higher than those of P. acidilactici J17. In all three strains, the superoxide dismutase (SOD) activity was higher in the cell-free supernatants than in the intracellular lysates. Among all three strains, P. acidilactici J17 showed the highest total antioxidant capacity (T-AOC) in the cell-free supernatant. Inoculating L. plantarum YX20 and P. acidilactici J17 increased lactic acid (LA) concentration and LAB counts, decreased dry matter (DM) loss, ammonia-N concentration, and pH, compared with control (CON) and L. plantarum XY15 inoculated alfalfa silages. After 1 d of ensiling, alfalfa silage inoculated with L. plantarum XY20 exhibited higher SOD activity than other silages. Inoculating L. plantarum XY20 and P. acidilactici J17 increased the DPPH free radical scavenging rates in alfalfa silage, compared with CON and L. plantarum XY15 inoculated 90 d-silages. Both L. plantarum YX15 and L. plantarum YX20 demonstrated a dual function of enhancing the lactic fermentation and improving the antioxidant status in alfalfa silage.